The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1302/2046-3758.94.bjr-2019-0149.r2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of femoral morphology and canal fill ratio on early radiological and clinical outcomes of uncemented total hip arthroplasty using a fully coated stem

Abstract: Aims The diversity of femoral morphology renders femoral component sizing in total hip arthroplasty (THA) challenging. We aimed to determine whether femoral morphology and femoral component filling influence early clinical and radiological outcomes following THA using fully hydroxyapatite (HA)-coated femoral components. Methods We retrospectively reviewed records of 183 primary uncemented THAs. Femoral morphology, including Dorr classification, canal bone ratio (CBR), canal flare index (CFI), and canal-calcar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…This study found that at a 5-year follow-up, patients with Dorr type A femurs had a 7.8% incidence of radiolucent lines compared with 2.5% (p < 0.001). Other studies of fully HA-coated stems of a comparable design ( 10 ) as well as proximally coated stems ( 11 , 12 ) reveal similar findings. Additionally, Magill et al ( 13 ) and Karayiannis et al ( 14 ) both report a statistical relationship between under-sizing the Corail stem and the development of radiolucent lines in zone 7.…”
Section: Discussionsupporting
confidence: 63%
“…This study found that at a 5-year follow-up, patients with Dorr type A femurs had a 7.8% incidence of radiolucent lines compared with 2.5% (p < 0.001). Other studies of fully HA-coated stems of a comparable design ( 10 ) as well as proximally coated stems ( 11 , 12 ) reveal similar findings. Additionally, Magill et al ( 13 ) and Karayiannis et al ( 14 ) both report a statistical relationship between under-sizing the Corail stem and the development of radiolucent lines in zone 7.…”
Section: Discussionsupporting
confidence: 63%
“…Ishi et al [ 18 ] showed that poor radiographic outcomes of uncemented stems were associated with a high canal flare index (CFI) and insufficient proximal filling, especially in Japanese women with narrow femoral canals. Similarly, D’Ambrosio et al [ 19 ] evaluated the influence of femoral morphology or femoral component filling on radiological outcomes following THA using a fully HA-coated femoral stem. In a series of 183 THAs, they found that femurs with either proximally flared or distally narrowed canals, or insufficient proximal filling, tend to have less favourable radiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The dimension of the implant was evaluated by radiographic measurement of the CFR [ 15 ] at 4 different levels on the postoperative radiograph: at the level of the lesser trochanter, 2 cm above and below the lesser trochanter and 7 cm below the lesser trochanter ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%